Análise funcional do gene órfão CcUNK8 de Coffea canephora via transformação genética de Setaria viridis - Duarte, Karoline Estefani (2014)
The coffee tree is one of the most valuable crops in the world economy, the reason why it has been the target of genetic improvement programmes performed aiming to insert new characters in the obtainment of plants containing superior agronomic characteristics such as greater drought tolerance. Because the conventional genetic improvement of coffee tree is time consuming, the use of the latest techniques in genomics is being developed to speed up the process of creating novel plants. Thus, the genome sequencing, and the large-scale sequencing of expressed genes becomes necessary for analyzing the genetic determinism of drought tolerance, and to identify candidate genes for this determinism. By analysing sequencing projects for crops such as Coffee spp., Arabidopsis thaliana and Oryza sativa was found a percentage of about 20-30% of no-hit genes, for which there is no similarity with sequences deposited in the GenBank. For Coffea canephora e Coffea arabica were identified and characterized several no-hit genes, such as the no-hit 33656, some of them have a expression profile on which it finds, in-silico, a heterogeneous distribution in relation to tissues and treatments. These no-hits may have originated from the processes of speciation, which could be linked to single response pathways of tolerant or susceptible organisms for a given condition. The no-hit CcUNK8 showed greater expression for material obtained from water-stressed leaves than from leaves of C. canephora. This no-hit is, thus, a candidate gene to drought tolerance, and was selected for genetic transformation using Setaria viridis as the model plant, in which was inserted the T-DNA containing this gene via Agrobacterium tumefaciens, and its expression was quantified by qPCR in the primary transformation events. In some of these events was found greater biomass accumulation for leaves and roots than for non-transformed individuals. Yet, by comparing the irrigated with the non-irrigated treatment, was found differences in the biomass accumulation within the same transformation event.